E Etika Tanggung Jawab Hans Jonas: Menyingkap Akar Persoalan Kerusakan Lingkungan Sebagai Dampak Ekspolitasi Freeport di Papua: Hans Jonas' Ethics of Responsibility: Revealing the Roots of the Problem of Environmental Damage as a Impact of Freeport Exploitation in Papua - Wiparlo, Valerianus; Pandor, Pius; Agu, Egidius (Jurnal Filsafat Indonesia, 2024)
This article discusses the phenomenon of environmental damage due to Freeport's mining exploitation in Papua. The activities of Freeport mining have caused environmental pollution in the Papua region. The purpose of this paper is to criticize Freeport's mining activities as actions that no longer consider the integrity of nature and society. The people are no longer seeing nature as the center and source of life but as a reality that serves human interests. Method used in this paper is a critical analysis of the phenomenon of environmental damage in Papua in terms of Hans Jonas' ethics of responsibility. Phenomena of environmental damage in Papua is a form of irresponsible actions carried out by PT Freeport which only focuses on fulfilling personal interests without considering the integrity of nature created in the future. Destroying nature is tantamount to destroying the future of mankind. The ethics of responsibility of Hans Jonas provides a new model of thinking for society and government institutions, namely that humans must preserve and maintain the integrity of nature as a form of responsibility for the sustainability of life in the present and future. The act of preserving the environment can only occur if there is fear (the fear heuristic) in every society to damage nature because nature basically has moral rights, and especially the act of destroying nature carried out by the community threatens the survival of Indonesian society in the future.